Electrochemiluminescent detection of Escherichia coli O157:H7 based on Ru(bpy)32+/ZnO nanorod arrays. (9th November 2018) - Liu, Danqing; Li, Tianchan; Huang, Weicheng; Ma, Zhuang; Zhang, Wei; Zhang, Rui; Yan, Hong; Yang, Bin; Liu, Shaoqin
Abstract: Foodborne pathogens are perpetual threats to human and animal health. Detection of pathogens requires accurate, sensitive, rapid and point-of-care diagnostic assays. In this study, we described a simple and sensitive electrochemiluminescent (ECL) assay to detect the deadly bacteria Escherichia coli O157:H7 by Ru ( bpy ) 3 2 + -coated ZnO nanorods arrays (NAs). The Ru ( bpy ) 3 2 + -coated ZnO NAs were fabricated by immobilizing Ru ( bpy ) 3 2 + on ZnO NAs with a large specific surface area and good conductivity. An Ru ( bpy ) 3 2 + -2-(dibutylamino)-ethanol (DBAE) system coated on ZnO NAs exhibits high ECL intensity, rapid response and good stability. This system was further developed as an ECL immunosensor used in the detection of E. coli O157:H7. The proposed ECL immunosensor exhibits a broad detection range within the scope of 200–100 000 CFU ml −1 and quite a low detection limit of 143 CFU ml −1 . The high specificity, remarkable reproducibility and good stability offer a sensitive, selective, and convenient pathway for detecting E. coli O157:H7 in the field of food safety and clinical diagnosis.